Analisis Yuridis Wakaf Tanah Negara dalam Perspektif Hukum Agraria dan Hukum Wakaf - Herlindah, Herlindah; Medaline, Onny; Maulana, Iqbal; Daud, Azzam Hasan (Pustaka Peradaban, 2025)
Waqf, as an instrument for the distribution of wealth in Islam, necessitates full ownership by the waqif over the dedicated asset, as stipulated in Article 1, Paragraph 1 of Law Number 41 of 2004 concerning Waqf. This establishes that a valid element of waqf is the asset being legally owned by the waqif. However, Article 11 of the Minister of Agrarian Affairs and Spatial Planning Regulation Number 2 of 2017 concerning Procedures for Waqf Land Registration stipulates that Waqf Land on State Land that has not been previously encumbered with any Land Right shall be registered as Waqf Land under the nazhir's name. Yet, within the National Agrarian Law system, the state only possesses public control over land and does not hold private ownership of State Land. Although the state is not explicitly mentioned as a waqif, the state's action, (as if) acting as a waqif, conceptually raises legal issues. This research analyzes the norm conflict regarding waqf of State Land from the perspectives of Agrarian Law and Waqf Law in Indonesia. It employs a normative legal research method with statutory and conceptual approaches. The analysis concludes that waqf of State Land without a prior concrete legal relationship with a legal subject as the waqif contradicts the principle of State Control Rights and the fundamental waqf principle of al-tamlik qabla al-tabarru’ (ownership before donation/waqf). This can lead to the non-fulfillment of waqf validity requirements. Therefore, it is necessary to pursue a mechanism for granting land ownership rights to qualified socio-religious legal entities to act as the waqif, followed by the waqf process. Wakaf, sebagai instrumen distribusi harta dalam Islam, mensyaratkan adanya kepemilikan penuh dari pihak wakif atas objek yang diwakafkan sebagaimana diatur dalam Pasal 1 angka 1 Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf. Bahwa salah satu unsur sahnya wakaf adalah harta benda yang dimiliki secara sah oleh Wakif. Namun, dalam Pasal 11 Peraturan Menteri Agraria dan Pertanahan Nasional Nomor 2 Tahun 2017 Tentang Tata Cara Pendaftaran Tanah Wakaf mengatur bahwa Tanah Wakaf atas Tanah Negara yang belum pernah dilekati dengan sesuatu Hak atas Tanah didaftarkan menjadi Tanah Wakaf atas nama Nazhir. Padahal dalam sistem Hukum Agraria Nasional, negara hanya berwenang menguasai tanah secara publik dan tidak memiliki secara keperdataan atas Tanah Negara. Meskipun tidak disebutkan secara eksplisit negara sebagai wakif, tindakan negara (seolah) sebagai wakif, secara konseptual menimbulkan persoalan. Penelitian ini menganalisis konflik norma tentang wakaf tanah yang berstatus tanah negara dalam perspektif Hukum Agraria dan Hukum Wakaf di Indonesia, menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil analisis menyimpulkan bahwa wakaf atas Tanah Negara tanpa lebih dulu adanya hubungan hukum kongkrit dengan subjek hukum sebagai wakif bertentangan dengan prinsip Hak Menguasai Negara dan Prinsip dasar wakaf, al-tamlik qabla al-tabarru’ (pemilikan sebelum hibah/wakaf). Hal ini dapat menimbulkan konsekuensi tidak terpenuhinya syarat sahnya wakaf. Oleh karena itu, perlu ditempuh mekanisme pemberian hak milik atas tanah kepada badan hukum sosial keagamaan yang memenuhi syarat untuk menjadi wakif yang kemudian dilanjutkan dengan proses wakaf.